Perbandingan Kapasitas Daya Dukung Fondasi Tiang Pancang Berdasarkan Pengujian Data Sondir dan Data N-SPT - M Sang Gumilar P; Rio Marpen; Kiki Rizky Amalia (Jurnal Talenta Sipil, 2022)
Rig was erected on a foundation that must be able to support the forces caused by the rig. The purpose of this research is to find out how big the difference between the axial and lateral bearing capacity of RIG ARJUNA #28 foundation. The research was conducted at RIG Arjuna #28 in Prabumulih City. In this research, an analysis of the carrying capacity of the pile foundation was carried out using Sondir and N-SPT data which will then be compared with the results of these calculations. It can be concluded that with data analysis using CPT/Sondir, the foundation will use 12 piles with a depth of 17 m, while using N-spt data the foundation will use 8 piles with a depth of 24 m.